RESPONSE OF RABI PIGEONPEA (Cajanas cajan (L.) Millsp) TO SOWING TIME AND IRRIGATIONS - P. VENKATA RAO (The Journal of Research ANGRAU, 2016)
A field experiment was conducted to study the impact of sowing time and supplemental irrigations on growth and yield of rabi pigeonpea at Regional Agricultural Research Station, Lam, Guntur. The results indicated that the response to supplemental irrigation was more when three irrigations were provided than that of two or one at critical growth stages of pigeonpea with respect to growth and yield components. The first fortnight of September is identified as an optimum time of sowing during post-rainy season with provision of three supplemental irrigations at critical growth stages. The highest grain yield (1973 kg ha-1) was recorded with this combination and it also gave higher net returns (Rs.73,861/-) and B:C ratio (1.29).